2001
DOI: 10.1007/bf02850298
|View full text |Cite
|
Sign up to set email alerts
|

Impulse magnetic-field therapy for migraine and other headaches: A double-blind, placebo-controlled study

Abstract: This double-blind, placebo-controlled study assessed the efficacy of 4 weeks of impulse magnetic-field therapy (16 Hz, 5 microTs), delivered through a small device, for different types of headache and migraine. Eighty-two patients were randomly assigned to receive either active treatment or placebo (n = 41 each) and were characterized according to one of seven diagnoses (migraine, migraine combined with tension, tension, cluster, weather-related, posttraumatic, or other). Efficacy was assessed in terms of dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…Clinical trials have been conducted to test magnetic field therapies in managing pain [39,40], tremor [41], epilepsy [42], and migraine headaches [43]. No data support their role in any illness.…”
Section: Energy Therapiesmentioning
confidence: 99%
“…Clinical trials have been conducted to test magnetic field therapies in managing pain [39,40], tremor [41], epilepsy [42], and migraine headaches [43]. No data support their role in any illness.…”
Section: Energy Therapiesmentioning
confidence: 99%
“…16 In another study, 76% of participants indicated that they were "clear" or "very clear" of their complaints about headaches, with no side effects from the treatment (4 weeks PEMF: 16 Hz, 5 microT), while no improvement was observed in the control group. 15 The effect of menstrual relationship on the intensity of migraine attacks and medication used for headache, may demonstrate that PEMF has little effect on the women's hormonal fluctuations that trigger the headaches in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Patients achieved over 70 percent improvement in their activity after using PEME. [15][16][17] Extremely low-frequency electromagnetic fields may have a beneficial effect in controlling migraines through several mechanisms. The exposure of neural and vascular cells to electromagnetic fields that resonate at 10 Hz can induce intracellular calcium oscillations and change the signaling cascades such as calcium-calmodulin-NO.…”
Section: Introductionmentioning
confidence: 99%
“…One study found symptom relief for 77 percent of participants in the treatment group, with 8 percent of controls reporting minor relief and 1 percent reporting moderate relief [11]. The study did not report any follow-up data.…”
Section: Pulsed Electromagnetic Fieldsmentioning
confidence: 90%
“…Several randomized, placebo-controlled trials were conducted with low-power PEMF devices that were worn near the head for approximately 1 month [11][12]. One study found symptom relief for 77 percent of participants in the treatment group, with 8 percent of controls reporting minor relief and 1 percent reporting moderate relief [11].…”
Section: Pulsed Electromagnetic Fieldsmentioning
confidence: 99%